ANALISIS ALGORITMA C.45 PADA APLIKASI MONITORING KINERJA DAN PENCAPAIAN ACCOUNT REPRESENTATIVE DI KANTOR XYZ - Elfaladonna, Febie; Novita, Nita; Amelia, Nyimas Rizki (ITB Ahmad Dahlan Jakarta, 2024)
Account Representative is a tax officer who is responsible for the implementation of services and direct supervision of a certain number of taxpayers who have been assigned as their responsibility. Monitoring account representative performance at XYZ Tax Office is less effective because performance and revenue data are updated and presented manually. To address this, the C4.5 Algorithm is proposed to support AR performance decision making. This algorithm forms a decision tree based on three main criteria: All AR Receipts, AR Receipts Per Person, and Target Receipts Per AR. The performance evaluation is performed incrementally based on these criteria. The test results showed that out of 34 account representatives, 14 achieved adequate performance, while 20 did not. Based on this, a decision tree was formed based on the calculation and analysis results of the C.45 algorithm.